A POTENT CYTOTOXICITY AND ANTIMICROBIAL ACTIVITY OF ZINC OXIDE NANOPARTICLES SYNTHESIZED BY LEAF OF IPOMOEA PES-CAPRAE (L.) R. BR. - RAMESH A; SUNDARRAJ P; BALAMANI J (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was conducted to investigate the cytotoxicity and antimicrobial activity of zinc oxide nanoparticles (ZnO NPs) synthesized as eco-friendly technique from the leaf extract of Ipomoea pes-caprae (L.) R. Br. against human lung adenocarcinoma (A549), brain tumor (U87) cells, and human pathogens Salmonella typhi, Staphylococcus aureus, Klebsiella pneumonia, Pseudomonas aeruginosa, and Bacillus subtilis. Materials and Methods: The work was carried out with varying precursor (plant extract) volume to optimize the synthesis of ZnO NPs and it was confirmed by ultraviolet (UV)-visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) analysis, scanning electron microscopy, and atomic force microscope (AFM) characterization techniques and evaluate its cytotoxicity activity by 3-(4,5-dimethyl-2- thiazolyl)-2,5-diphenyl–tetrazolium bromide assay method, antimicrobial activity by disk diffusion method. Results: A peak at 320 nm with maximum intensity was observed at temperature of 80°C with pH of 8.0 in UV-visible spectroscopy confirmed the formation of ZnO NPs and we calculate the size of ZnO NPs from XRD data found as 15.8 nm. The FTIR analysis evaluated that the presence of different functional groups is carboxyl, amine, and phenolic compounds of leaves extract which are involved in the reduction of zinc ions and acts as capping the ZnO NPs. AFM microgram confirms that ZnO NPs were in nanorange and spherical in nature. The cytotoxicity activity of A549 and U87 cell lines treated with various concentrations of ZnO NPs showed a dose-dependent increase in cell inhibition and the half maximal inhibitory concentration value was calculated to be 7.8 μg/ml. The antibacterial activity of selected pathogens shows higher zone of inhibition. Conclusion: The present study reveals that synthesized ZnO NPs capping with various bioactive compounds present in the leaf of I. pes-caprae show promising activity of cancer cell lines and antimicrobial agents; hence, further detailed study may lead to develop at a novel phytomedicine for the anticancer and antimicrobial drugs.